A descriptive analysis of the ethnic/racial composition of texas high school teachers and students: A multiyear study - Moye, Alan K; Slate, John R (American Journal of Social Sciences and Humanities, 2023)
The purpose of this longitudinal, statewide, descriptive analysis was to examine the high school teacher and student ethnic/racial diversity for the 2010-2011 school year through the 2018-2019 school year. Data were obtained from the Texas Education Agency on all student enrollment and on all teacher employment. As such, a causal-comparative longitudinal descriptive research design was present due to the use of archival data. Consistent decreases were observed in the average percentages of both White teachers and White students over the 9 school years of data that were examined. Consistent increases were documented in the average percentages of both Hispanic teachers and students over the 9 school years. Slight but consistent increases were established in the average percentages of Asian teachers and students and of Black teachers. The average percentage for Black students decreased in all school year examined, with the exception of two school years. Inequities existed as several school years of data analyzed revealed greater average percentages for ethnic/racial minority students when compared to ethnic/racial minority teachers. Also provided within this study are recommendations for future research along with implications for local and statewide policy and practice.